Some characteristics of woody plants inhabited by Viscum album (Santalaceae) in the city of Kyiv - Bilonozhko Yu.O.; Kalafat L.O.; Rabokon A.M.; Postovoitova A.S.; Privalikhin S.M.; Demkovych A.E.; Pirko Ya.V. (Ukrainian Botanical Journal, 2022)
As a result of the study, a wide range of tree species parasitized by white mistletoe (Vіscum album) in the city of Kyiv, Ukraine, was identified. Some species, such as Quercus robur, Ulmus pumila, and Alnus glutinosa, remained uninfested even in the case of a high degree of infestation of surrounding trees. It has been found that among the infested plants only 4.34% of deciduous species and 5.05% of conifers demonstrated a severe damage caused by the hemiparasite (more than 20 plants of V. album in one crown). The largest number of trees and the highest level of damage were observed for Acer saccharinum, A. platanoides, Salix alba, Robinia pseudoacacia, Populus nigra, Tilia cordata, and Betula pendula aged in average 45–50 years. In the study of genetic characteristics of affected and unaffected by V. album trees of Pinus sylvestris at the molecular level by TBP markers, no differences have been revealed.